Let us conserve and exchange seeds: celebrating traditional crop diversity of the Nepali lowlands - Vernooy, Ronnie; Shrestha, P.; Gauchan, D.; Bhusal, A.; Gurung, R.; Pudasaini, N.; Community Seed Banks Association of Nepal (2019)
A seed fair is an activity to create awareness about and appreciate local crop diversity, exchange seed and related knowledge, and celebrate farmers’ efforts to conserve agrobiodiversity. It takes considerable time and effort to organize a seed fair. This brief describes the seed fair organized at the Agyauli Community Seedbank, Nawalparasi in the southern region of Nepal.